Kombinasi Proses Presipitasi dan Adsorpsi untuk Menangani Limbah Bahan Berbahaya Beracun (B3) Hasil Kegiatan Analisis di Laboratorium Analisis Polinela - Ismadi Raharjo; Didik Kuswadi (Jurusan Teknologi Pertanian, 2020)
The objectives of this research to determine the combination of the process of precipitation and adsorption in reducing the content of pollutant metals in the hazardous waste category B3 (hazardous toxic substances) produced at the Polinela Analysis Laboratory. The study was conducted in May to November 2019. The results obtained from 3 (three) times of sampling in May 2019 obtained a description of the characteristics of heavy metal content in wastewater in the form of Aluminum (Al) an average of 1.59 ppm, iron content ( Fe) an average of 9.73 ppm and Cadmium (Cd) an average of 0.022 ppm. From these results it can be seen that the wastewater containing Al and Fe has passed the threshold quality standard of waste water that is allowed to be discharged into water resource (PP No.82 of 2001), while the Cd content is still below the threshold. Furthermore, through the precipitation process with Ca (OH)2 0.8 M and adsorption using activated charcoal with contact time of 3 (three) hours the content of pollutants in wastewater can be reduced to 0.92 ppm for Al metals and 0.1 ppm for metals Fe, so that it is below the standard quality of waste water that is allowed to drain in water. Keywords: adsorption, precipitation, quality standard